Rubber mixtures and vehicle tires

CN123022748APending Publication Date: 2026-10-30CONTINENTAL REIFEN DEUTSCHLAND GMBH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202580024456.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-25
Filing Date
2025-03-06
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

增加硫网络的效率通常改善耐久性(老化稳定性),但滚动阻力变得更差

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a sulfur-crosslinkable rubber mixture, in particular for flange profiles for vehicle tires, comprising at least the following ingredients: - at least one diene rubber, - 40 to 90 phr (parts by weight based on 100 parts by weight of the total rubber in the mixture) of at least one carbon black, wherein one or more of the carbon blacks have an average iodine number of 55 to 80 g / kg according to ASTM D 1510, - 5 to 20 phr of at least one silica, - at least one silane coupling agent, and - an effective vulcanization system comprising at least one vulcanization accelerator and elemental sulfur, wherein the mass ratio of vulcanization accelerator to sulfur is 8:1 to 3:1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a sulfur-crosslinkable rubber compound, particularly for flange profiles of vehicle tires.

[0002] The present invention further relates to a vehicle tire having at least one component composed of such a sulfur-vulcanized rubber mixture. Background Technology

[0003] Different requirements are imposed on different components of vehicle tires, especially pneumatic vehicle tires. This is accompanied by the fact that a wide variety of mixture compositions are used for various components. These mixture compositions can, in turn, be affected by the type and amount of different mixture components in terms of their mixture and vulcanized rubber properties. However, improving one property through changes in mixture composition often leads to the deterioration of another property. Two often contradictory properties are, for example, rolling resistance and durability.

[0004] Rolling resistance and durability can be influenced, for example, by the nature and amount of the fillers and crosslinking systems used. Rubber compounds in vehicle tires are typically reinforced with fillers, typically carbon black and / or silica. Changing the type of carbon black to one with a lower surface area generally results in, for example, a reduction in hysteresis (associated with improved rolling resistance), but simultaneously leads to a deterioration of properties important for durability. On the other hand, changing from a type of carbon black with a lower surface area to one with a higher surface area improves durability but results in poorer hysteresis.

[0005] The term "sulfur-crosslinked rubber compound" as used above should be understood to refer to a rubber compound produced by sulfur vulcanization of a ready-to-use rubber compound (or raw rubber compound). Therefore, a sulfur-crosslinked rubber compound is a vulcanized rubber. All descriptions also apply to vehicle tires according to the invention, which contain at least one rubber compound according to the invention in at least one component. Descriptions of individual components refer to the rubber compound before vulcanization, i.e., a sulfur-crosslinkable rubber compound, unless otherwise stated. It will be apparent to those skilled in the art that these components may exist in altered forms after vulcanization, and this applies particularly to the rubber (polymer), sulfur, and other components involved in vulcanization.

[0006] Rubber compounds used in vehicle tires are typically crosslinked with sulfur, where the ratio of vulcanization accelerator to sulfur determines the efficiency of the sulfur network. If the ratio is low, below 1:2, it is considered conventional vulcanization and long sulfur chains are present. At higher ratios, efficient vulcanization systems exist and the sulfur chains are shorter. Increasing the efficiency of the sulfur network generally improves durability (aging stability), but rolling resistance becomes worse.

[0007] High durability, particularly aging stability, is especially important in the bead area of ​​pneumatic vehicle tires, where high mechanical and thermal stresses occur. Simultaneously, rolling resistance should be minimized. Particularly stressful areas of pneumatic vehicle tires include the flange profiles, also known as rim strips or bead protection strips, which are also partially in direct contact with the outside air.

[0008] For example, rubber compounds for tire bead regions are known from EP 3632975 A1. The compound described therein comprises natural rubber, polybutadiene, two different carbon blacks, and a sulfur vulcanization system.

[0009] WO 2020065175 A1 discloses mixtures for use in the bead area, which contain natural rubber, carbon black and silica greater than 30 phr, as well as conventional vulcanization systems. Summary of the Invention

[0010] One object of the present invention is to provide a rubber compound characterized by improved durability and reduced hysteresis of the vulcanized rubber, and thus resulting in an improved trade-off between durability and rolling resistance when used, for example, in tires.

[0011] This objective is achieved according to the invention by a sulfur-crosslinkable rubber compound (particularly for flange profiles of vehicle tires), which contains at least the following components:

[0012] - At least one diene rubber

[0013] At least one carbon black having a phr of -40 to 90 phr (based on the weight of 100 parts by weight of total rubber in the mixture), wherein one or more carbon blacks have an average iodine value of 55 to 80 g / kg according to ASTM D 1510.

[0014] At least one type of silica with a phr of -5 to 20 phr

[0015] - at least one silane coupling agent, and

[0016] - An effective vulcanization system containing at least one vulcanization accelerator and elemental sulfur, wherein the mass ratio of the vulcanization accelerator to sulfur is 8:1 to 3:1.

[0017] It has been unexpectedly found that one or more carbon blacks with an average iodine value between 55 and 80 g / kg, combined with small amounts of silica and silane coupling agents, and specific combinations of specific effective vulcanization systems in specified amounts under each condition, produce diene rubber mixtures that result in high durability of the vulcanized rubber by improving aging stability while reducing hysteresis.

[0018] The unit “phr” (parts by weight of rubber) used in this document is the standard unit for quantities in rubber industry formulations. Dosage of individual substances by weight is always based on 100 parts by weight of the total mass of all solid rubber present in the mixture.

[0019] According to the present invention, the rubber mixture comprises at least one diene rubber. Diene rubber refers to rubber formed by polymerization or copolymerization of dienes and / or cycloolefins and thus having C=C double bonds in the main chain or side groups. The diene rubber may be functionalized, modified, or coupled.

[0020] The diene rubber is preferably selected from the group consisting of: natural polyisoprene (NR), synthetic polyisoprene (IR), epoxidized polyisoprene (ENR), butadiene rubber (BR), butadiene-isoprene rubber, styrene-butadiene rubber (SBR) (especially solution-polymerized styrene-butadiene rubber (SSBR) and emulsion-polymerized styrene-butadiene rubber (ESBR)), styrene-isoprene rubber, and a molecular weight M greater than 20,000 g / mol. w Liquid rubber, halogenated butyl rubber, polynorbornene, isoprene-isobutylene copolymer, ethylene-propylene-diene rubber, nitrile rubber, chloroprene rubber, acrylate rubber, fluororubber, silicone rubber, polysulfide rubber, epichlorohydrin rubber, styrene-isoprene-butadiene terpolymer, hydrogenated acrylonitrile-butadiene rubber, and hydrogenated styrene-butadiene rubber.

[0021] Nitrile rubber, hydrogenated acrylonitrile-butadiene rubber, chloroprene rubber, butyl rubber, halogenated butyl rubber, or ethylene-propylene-diene rubber are used particularly in the production of industrial rubber products such as belts, drive belts, hoses, and / or shoe soles. Preferably, mixtures of these rubbers are used herein, which are specific in terms of fillers, plasticizers, vulcanization systems, and additives, and are known to those skilled in the art.

[0022] In a particularly preferred embodiment of the invention, the diene rubber is selected from the group consisting of: natural polyisoprene (NR), synthetic polyisoprene (IR), butadiene rubber (BR), solution-polymerized styrene-butadiene rubber (SSBR), and emulsion-polymerized styrene-butadiene rubber (ESBR). Natural polyisoprene should be understood to mean rubber obtained from sources such as rubber trees (Hevea brasiliensis) or non-rubber tree sources (e.g., sagebrush or dandelion (e.g., rubber grass (Taraxacum koksaghyz))). Natural polyisoprene (NR) should be understood to mean non-synthetic polyisoprene.

[0023] The butadiene rubber (= BR, polybutadiene) optionally present in the rubber mixture according to the invention can be of any type known to those skilled in the art. These particularly include so-called high-cis and low-cis types, wherein polybutadiene having a cis content of not less than 90% by weight is called high-cis type, and polybutadiene having a cis content of less than 90% by weight is called low-cis type. An example of low-cis polybutadiene is Li-BR (lithium-catalyzed butadiene rubber) having a cis content of 20% to 50% by weight. Particularly good properties and low hysteresis are achieved with high-cis BR.

[0024] One or more polybutadienes used can be end-group modified and / or functionalized along the polymer chain by modification and functionalization. Modification can be performed with hydroxyl and / or ethoxy and / or epoxy and / or siloxane and / or amino and / or aminosiloxane and / or carboxyl and / or phthalocyanine and / or sulfide silane. However, other modifications known to those skilled in the art, also referred to as functionalization, are also suitable. Metal atoms can be components of such functionalization.

[0025] When at least one styrene-butadiene rubber (styrene-butadiene copolymer) is present in the rubber mixture, this styrene-butadiene rubber can be solution-polymerized styrene-butadiene rubber (SSBR) and emulsion-polymerized styrene-butadiene rubber (ESBR), wherein a mixture of at least one SSBR and at least one ESBR is also acceptable. The terms "styrene-butadiene rubber" and "styrene-butadiene copolymer" are used synonymously in the context of this invention.

[0026] The styrene-butadiene copolymer used can be end-group modified and / or functionalized along the polymer chain through the modifications and functionalizations listed above for polybutadiene.

[0027] For the use of a rubber compound in the bead-adjacent area of ​​a pneumatic vehicle tire, the rubber compound preferably contains 20 to 50 phr of natural rubber (NR) and 50 to 80 phr of at least one butadiene rubber (BR).

[0028] The rubber compound according to the invention contains at least one carbon black of 40 to 90 phr, preferably 50 to 80 phr, wherein one or more carbon blacks have an average iodine value of 55 to 80 g / kg according to ASTM D 1510. Therefore, it is possible to use carbon black having an iodine value of 55 to 80 g / kg according to ASTM D 1510, such as N351 type carbon black (iodine value: 68 g / kg), in the compound. However, it is also possible to use two or more carbon blacks in the compound in such a way that an average iodine value of 55 to 80 g / kg according to ASTM D 1510 is obtained. A mixture of multiple carbon blacks (blended compound) is then used.

[0029] The rubber compound contains at least one type of silica at 5 to 20 phr. Any silica known to those skilled in the art may also be used, and these may also be used in mixtures. Preferred silica is silica having a nitrogen surface area (BET surface area) of 35 to 400 m² / g (according to DIN ISO 9277 and DIN 66132) and a CTAB surface area of ​​30 to 400 m² / g (according to ASTM D 3765). Therefore, the silica that can be used includes, for example, not only those of the Ultrasil® VN3 (trade name) type from Evonik, but also silica such as Zeosil® 1115 or Zeosil® 1085 from Solvay, as well as highly dispersible silica, so-called HD silica (e.g., Zeosil® 1165 MP from Solvay).

[0030] For sustainability purposes, and to improve the mixture, the mixture preferably contains silica produced from rice husk ash (“rice husk ash silica” (RHAS)).

[0031] To improve processability and bond silica to the diene rubber of the mixture, the mixture contains at least one silane coupling agent, which is preferably used in the rubber mixture at an amount of 1-15 phf (parts by weight, based on 100 parts by weight of silica). The silane coupling agent may also be used as a mixture.

[0032] The expression phf (parts per hundred parts by weight of filler) used in this document is a unit commonly used in the rubber industry for the amount of coupling agents used for polar fillers. In the context of this application, phf refers to the presence of silica, meaning that any other filler present (such as carbon black) is not included in the calculation of the amount of silane coupling agent.

[0033] During the mixing (in situ) of rubber / rubber blends or in the case of pretreatment (pre-modification) prior to the addition of fillers to the rubber, silane coupling agents react with surface silanol groups or other polar groups on silica. Silane coupling agents that can be used herein include all silane coupling agents known to those skilled in the art for use in rubber blends. Such coupling agents known from the prior art are bifunctional organosilanes having at least one alkoxy, cycloalkoxy, or phenoxy group as a leaving group on a silicon atom and a group as another functional group that can optionally undergo a chemical reaction with the double bond of the polymer after cleavage. The latter group may include, for example, chemical groups such as -SCN, -SH, -NH2, or -S. x - (where x = 2-8). Therefore, usable silane coupling agents include, for example, 3-mercaptopropyltriethoxysilane, 3-thiocyanopropyltrimethoxysilane, or 3,3'-bis(triethoxysilylpropyl) polysulfides having 2 to 8 sulfur atoms, such as 3,3'-bis(triethoxysilylpropyl)tetrasulfide (TESPT), the corresponding disulfide, or other sulfides having 1 to 8 sulfur atoms in mixtures with various amounts of various sulfides. TESPT can also be added, for example, as a mixture with industrial carbon black (trade name X50S from Degussa). Block mercaptosilanes, as known from, for example, WO 99 / 09036, can also be used as silane coupling agents. Silanes as described in WO 2008 / 083241 A1, WO 2008 / 083242 A1, WO 2008 / 083243 A1, and WO 2008 / 083244 A1 can also be used. For example, silanes under the name NXT can be used. ® The following are silanes sold by Momentive, USA, in various variants, or by Evonik Industries under the name VP Si 363. They are also described as "silated core polysulfides" (SCP, polysulfides with a silylated core), as specified in, for example, US 20080161477 A1 and EP 2 114 961 B1.

[0034] Rubber blends may contain conventional amounts of additional fillers, such as aluminosilicates, kaolin, chalk, starch, magnesium oxide, titanium dioxide, rubber gels and fibers (e.g., aramid fibers, glass fibers, carbon fibers, cellulose fibers), carbon nanotubes (including discrete CNTs, so-called hollow carbon fibers (HCFs) and modified CNTs containing one or more functional groups such as hydroxyl, carboxyl and carbonyl groups), graphite, graphene or so-called “carbon dioxide biphase fillers”, wherein these fillers may be used in combination.

[0035] Crucially for this invention, the rubber compound comprises an effective vulcanization system containing at least one vulcanization accelerator and elemental sulfur, wherein the mass ratio of the vulcanization accelerator to sulfur is 8:1 to 3:1, preferably 7:1 to 3:1, and particularly preferably 6:1 to 3.5:1. This allows for crosslinking with short sulfur chains to form an effective network.

[0036] The vulcanization accelerator can be selected from any vulcanization accelerator known to those skilled in the art for use in sulfur vulcanization. This group of accelerators includes thiazole accelerators, mercapto accelerators, sulfenamide accelerators, sulfenylimide accelerators, thiocarbamate accelerators, thiuram accelerators, thiophosphate accelerators, thiourea accelerators, xanthate ester accelerators, and guanidine accelerators. For particularly good durability at low rolling resistance, one or more vulcanization accelerators are preferably selected from the group consisting of mercapto accelerators, sulfenamide accelerators, sulfenylimide accelerators, and guanidine accelerators.

[0037] In an advantageous embodiment of the invention, the sulfur-crosslinkable rubber mixture contains at least TBSI (N-tert-butyl-2-benzothiazole sulfenamide) and / or TBBS (N-tert-butyl-2-benzothiazole sulfenamide) and / or DCBS (N,N-dicyclohexyl-2-benzothiazole sulfenamide) and / or CBS (N-cyclohexyl-2-benzothiazole sulfenamide) as vulcanization accelerators.

[0038] All vulcanization accelerators can also be used in mixtures.

[0039] For good aging stability of vulcanized rubber, the rubber compound preferably contains 0.5 to 1.5 phr of sulfur.

[0040] Rubber compounds may also contain vulcanization inhibitors.

[0041] The terms “vulcanized” and “crosslinked” are used synonymously in the context of this invention.

[0042] The rubber mixture according to the invention may also contain different plasticizers. These are preferably present in the mixture in an amount of up to 50 phr.

[0043] The plasticizers used include, for example, those selected from the group consisting of: plasticizers derived from renewable raw materials, such as rapeseed oil or sunflower oil or rubber-derived liquid oil (RTL) or biomass-derived liquid oil (BTL), preferably having a polycyclic aromatic hydrocarbon content of less than 3% by weight according to method IP 346, or especially resin acids or ointments or their average molecular weight (based on BS ISO 11344:2004, determined by GPC = gel permeation chromatography) between 500 and 20000 g / mol, mineral oils, phosphate esters such as tris(2-ethylhexyl) phosphate, and liquid polymers having a weight-average molecular weight distribution M of 60000 g / mol or less according to GPC. w Liquid polymers. If additional liquid polymers are used as plasticizers in the rubber mixture according to the invention, these are not included as rubber in the calculation of the composition of the polymer matrix. Preferably, DAE (distilled aromatic extract), RAE (residual aromatic extract), TDAE (treated distilled aromatic extract), MES (mild extraction solvent), rapeseed oil and / or liquid diene polymers are used.

[0044] The rubber compound may further contain conventional additives in conventional weight fractions, preferably added during at least one primary mixing stage in the production of the compound. These additives include...

[0045] a) Aging stabilizers, such as N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (6PPD), N,N'-diphenyl-p-phenylenediamine (DPPD), N,N'-xylyl-p-phenylenediamine (DTPD), N-isopropyl-N'-phenyl-p-phenylenediamine (IPPD), N,N'-di(1,4-dimethylpentyl)-p-phenylenediamine (77PD), N,N'-di(1-ethyl,4-methylhexyl)-p-phenylenediamine (88PD), N,N'-bis(1-ethyl-3-methylpentyl)-p-phenylenediamine (DOPD), and N,N'-di-β-naphthyl-p-phenylenediamine (DNPD), and 2,2,4-trimethyl-1,2-dihydroquinoline (TMQ).

[0046] b) Activators, such as zinc oxide (e.g., ZnO particles or powder); conventionally used zinc oxide typically has a BET surface area of ​​less than 10 m² / g. However, it is also possible to use zinc oxide with a BET surface area of ​​10 to 100 m² / g (e.g., so-called "nano zinc oxide") and fatty acids (e.g., stearic acid) or zinc complexes, such as zinc ethylhexanoate.

[0047] c) Resins, such as phenolic resins, especially tackifying resins. The tackifying resin used can be a natural or synthetic resin that acts as a tackifier, such as a hydrocarbon resin. The hydrocarbon resin can be phenolic, aromatic, or aliphatic. The tackifying resin is preferably selected from the group consisting of: rosin and its esters, terpene-phenol resins, acetylenic-phenol resins, phenolic resins, and coumarone-indene resins, wherein phenolic resins are particularly suitable for this invention.

[0048] d) Plasticizing aids, such as 2,2'-dibenzoylaminodiphenyl disulfide (DBD), and

[0049] e) Processing aids, such as fatty acid salts, such as zinc soaps, and fatty acid esters and their derivatives.

[0050] The total amount of other additives is 3 to 150 phr, preferably 3 to 100 phr and particularly preferably 5 to 80 phr.

[0051] The production of rubber compounds is carried out using methods conventional in the rubber industry, in which a primary mixture containing all components except for the vulcanization system (sulfur and substances affecting vulcanization) is initially produced in one or more mixing stages. A ready-to-use compound is produced by adding the vulcanization system in the final mixing stage. This ready-to-use compound is then subjected to further processing, such as by extrusion, and shaped into a suitable form. This is followed by further processing by vulcanization, where sulfur crosslinking occurs due to the addition of the vulcanization system in the context of this invention.

[0052] Rubber blends can be used in a wide variety of rubber products, where low hysteresis, high durability, and aging stability are advantageous. Rubber blends are preferably used in the production of vehicle tires, such as passenger car tires, van tires, truck tires, or two-wheeled vehicle tires. The blends can be used in different components of vehicle tires, especially pneumatic vehicle tires. The blends involved can be, for example, blends in areas of the bead and sidewall, such as the cam, portions of the cam, portions of the sidewall, or crescent-shaped inserts in the sidewall area.

[0053] The rubber compound is preferably used as the flange profile of vehicle tires, especially pneumatic vehicle tires. Tires having a flange profile made of the compound according to the invention are characterized by low rolling resistance and high durability.

[0054] In the production of pneumatic vehicle tires, the mixture is shaped as a ready-to-use mixture before vulcanization into the shape of relevant components (e.g., flange profiles) and applied in a known manner in the production of green vehicle tires.

[0055] This invention covers all advantageous configurations, particularly those reflected in the claims. It also covers configurations resulting from combinations of different features (e.g., components of a rubber compound) with varying levels of preference, such that the invention also captures combinations of a first feature described as “preferred” or, in advantageous embodiments, a feature described as “particularly preferred” with other features, such as those described as “particularly preferred.” Detailed Implementation

[0056] The present invention will now be described in more detail with reference to the comparative examples and working examples summarized in Table 1.

[0057] The comparative mixture is denoted as V, and the mixture of the present invention is denoted as E.

[0058] The mixture is produced in three stages in a laboratory mixer under conventional conditions using methods commonly employed in the rubber industry. Initially, all components except the vulcanizing system (sulfur and substances affecting vulcanization) are mixed in the first two mixing stages (primary mixing stages). In the third stage (final mixing stage), the vulcanizing system is added to obtain a ready-to-use mixture, where mixing is carried out at 90°C to 120°C.

[0059] All the mixtures were further used to produce test samples by vulcanizing at 160°C under pressure for 15 minutes. These test samples were then used to determine typical material properties for the rubber industry by the test methods specified below:

[0060] - Network node spacing via differential scanning calorimetry: This utilizes the fact that the liquid-solid phase transition of the swelling agent in a swollen polymer network depends on the crosslinking density. Samples of the corresponding rubber mixtures were swollen using cyclohexane as the swelling agent; for this purpose, the corresponding samples were extracted with cyclohexane and then allowed to stand at room temperature (RT) for further swelling. The freezing point of cyclohexane in the network was then determined to be lower than that of the macroscopically expanded liquid phase: the prepared samples were cooled in a measuring device and the heat flux was recorded. This resulted in two freezing peaks, one for pure cyclohexane at approximately 3°C and another for cyclohexane present in the swollen sample. The network node spacing was calculated from the temperature difference.

[0061] -Shore A hardness at room temperature according to ISO 868

[0062] -Resilience at 70°C according to ISO 4662

[0063] - Elongation at break at room temperature according to DIN 53504. Samples were measured before and after aging: in each case, aged in air at 80°C for 14 days.

[0064] - Fatigue cracking resistance (fatigue cracking life), defined as the number of load changes in thousands of cycles (kC) under constant, repeated strain cycles at a frequency of 10⁴ ± 8 min⁻¹ until the dumbbell-shaped sample fractures, is determined using a Monsanto Fatigue Fracture Tester (FTF) at room temperature (RT, 23°C ± 2°C). Samples were measured before and after aging: in each case, samples were aged in air at 80°C for 14 days. Unaged samples were measured at 89% pre-strain, and aged samples were measured at 61% pre-strain.

[0065] When a compound is used in pneumatic vehicle tires, high resilience at 70°C (synonymous with reduced hysteresis) can be associated with low rolling resistance.

[0066] Table 1

[0067]

[0068] a High cis polybutadiene rubber

[0069] b N339 carbon black, iodine value: 90 g / kg

[0070] c Carbon black N351, iodine value: 68 g / kg

[0071] d Ultrasil ® VN3, Evonik, nitrogen surface area = 180 m² 2 / g, CTAB 165 m 2 / g

[0072] e TESPD (3,3'-bis(triethoxysilylpropyl)disulfide), Si266, Evonik Industries

[0073] f N-tert-butyl-2-benzothiazole sulfenamide

[0074] The data in Table 1 illustrate the effects of individual measures (effective vulcanization system only (2(V)), carbon black with only average iodine value only (3(V)), silica with only silane coupling agent (4(V))) and combined measures (carbon black with average iodine value and silica with silane coupling agent (5(V))). None of the comparative mixtures simultaneously achieved the goals of high durability (obvious from the elongation at break values) even after aging and low rolling resistance (derived from the resilience value at 70°C).

[0075] Surprisingly, only the special mixture 6(E) can resolve this trade-off. The resilience at 70°C and the elongation at break under both aged and non-aged conditions are well beyond the expected results of the respective individual measures.

[0076] The significant improvement in durability was also evident in the markedly improved resistance to fatigue cracking, especially after aging. The sample made from the special mixture 6 (E) unexpectedly withstood significantly more load cycles than all other samples after aging, reaching 70 kC.

Claims

1. A sulfur-crosslinkable rubber compound, particularly for flange profiles of vehicle tires, comprising at least the following components: - At least one diene rubber At least one carbon black having a phr of -40 to 90 phr (based on the weight of 100 parts by weight of total rubber in the mixture), wherein the one or more carbon blacks have an average iodine value of 55 to 80 g / kg according to ASTM D 1510. At least one type of silica with a phr of -5 to 20 phr - at least one silane coupling agent, and - An effective vulcanization system containing at least one vulcanization accelerator and elemental sulfur, wherein the mass ratio of the vulcanization accelerator to sulfur is 8:1 to 3:

1.

2. The sulfur-crosslinkable rubber compound as described in claim 1, characterized in that, The sulfur-crosslinkable rubber compound contains at least one carbon black at 50 to 80 phr, wherein the one or more carbon blacks have an average iodine value of 55 to 80 g / kg according to ASTM D 1510.

3. The sulfur-crosslinkable rubber compound as described in claim 1 or 2, characterized in that, This sulfur-crosslinkable rubber compound contains silica produced from rice husk ash ("rice husk ash silica" (RHAS)).

4. The sulfur-crosslinkable rubber compound as described in at least one of the preceding claims, characterized in that, The rubber compound contains at least one silane coupling agent at a concentration of 1-15 phf (based on 100 parts by weight of silica).

5. The sulfur-crosslinkable rubber compound as described in at least one of the preceding claims, characterized in that, The mass ratio of vulcanization accelerator to sulfur is 7:1 to 3:1, preferably 6:1 to 3.5:

1.

6. The sulfur-crosslinkable rubber compound as described in at least one of the preceding claims, characterized in that, The one or more vulcanization accelerators are selected from the group consisting of: thiol accelerators, sulfenamide accelerators, sulfenamide accelerators, and guanidine accelerators.

7. The sulfur-crosslinkable rubber compound as described in at least one of the preceding claims, characterized in that, The sulfur-crosslinkable rubber compound contains at least TBSI (N-tert-butyl-2-benzothiazole sulfenamide) and / or TBBS (N-tert-butyl-2-benzothiazole sulfenamide) and / or DCBS (N,N-dicyclohexyl-2-benzothiazole sulfenamide) and / or CBS (N-cyclohexyl-2-benzothiazole sulfenamide) as vulcanization accelerators.

8. The sulfur-crosslinkable rubber compound as described in at least one of the preceding claims, characterized in that, The sulfur-crosslinkable rubber compound contains 0.5 to 1.5 phr of sulfur.

9. The sulfur-crosslinkable rubber compound as described in at least one of the preceding claims, characterized in that, This sulfur-crosslinkable rubber compound contains -20 to 50 phr natural rubber (NR) and At least one butadiene rubber (BR) with a phr of -50 to 80 phr.

10. A vehicle tire comprising at least one component made of a sulfur-vulcanized rubber compound as claimed in any one of claims 1 to 9.

11. The vehicle tire of claim 10, particularly a pneumatic vehicle tire, wherein the flange profile is composed of a sulfur-crosslinked rubber mixture as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silated core polysulfides, their preparation and use in filled elastomer compositions

    EP2114961B1

  • Rubber composition and pneumatic tire

    EP3632975A1

  • Silated core polysulfides, their preparation and use in filled elastomer compositions

    US20080161477A1

  • Blocked mercaptosilane coupling agents for filled rubbers

    WO1999009036A1

  • Tire compositions and components containing free-flowing filler compositions

    WO2008083241A2